Warmer Water Affects Immunity of a Tolerant Reef Coral - Palmer, Caroline V. (Frontiers in Marine Science, 2018)
Corals are multipartite sedentary organisms, which have evolved complex, physiological networks in order to survive perturbations and environmental fluctuations. However, climate change is warming tropical waters, pushing the limits of coral tolerance and driving global declines. Coral susceptibility to thermal anomalies is variable among species and through time, and directly relates to constituent immunity. Constituent immunity refers to immune activities required to ensure homeostasis, whereas an immune response is acutely heightened immune activity to a perturbation. Understanding the mechanisms behind coral health, and sustained health through adverse conditions, is increasingly important for establishing effective reef conservation and restoration projects. However, most experimental studies of coral health use species that are highly susceptible to thermal events, potentially skewing our understanding. To determine the influence of warmer water on immunity, activities of key coral immune pathways and an antioxidant were compared under ambient (27 ºC) and warmer water (32 ºC), and between injured and uninjured (control) branches of the tolerant reef coral Porites cylindrica. Three types of phenoloxidase, mono-phenoloxidase, ortho-diphenoloxidase and para-diphenloxidase, indicative of two melanin synthesis pathways (the tyrosinase and laccase-type), and peroxidase were measured at 0 (control), 1, 6, 24, 48 and 168 h post-injury. All four enzymes demonstrated consistent levels of activity under ambient conditions (27 ºC), indicating constituent immunity. Upon injury at ambient temperature, all enzyme activities were significantly higher 1 h post-injury as compared to uninjured controls, demonstrating a comprehensive immune response to tissue disruption. Under warmer water, constituent immunity increased through time indicative of immune modulation to maintain homeostasis. However, warmer water, within the non-bleaching summer range, suppressed the immune response to injury, delaying it by 24 hrs. Therefore, upon the environmental cue of warmer water, the tolerant coral P. cylindrica may divert resources away from immune responses (immunosuppression) while enhancing constituent immunity (immune modulation) so as to maintain health through sub-optimal conditions. These changes in immunity with warmer water demonstrates that temperature affects coral immunity and, for this tolerant coral, triggers immune-modulation that may provide cross-tolerance to perturbations more frequent in summer months, such as bleaching and disease.